2001
DOI: 10.7863/jum.2001.20.12.1277
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of normal intrauterine cavity sonographic findings after first‐trimester abortion.

Abstract: Objective. To characterize the sonographic appearance of the uterine cavity after uncomplicated firsttrimester abortion. Methods. Women who underwent uterine evacuation for first-trimester abortion were referred for endovaginal sonographic examination within the week after the procedure. Special attention was directed to characterizing the intrauterine cavity. Demographic and clinical parameters were collected. A repeated postmenstrual examination was carried out in selected cases. Results. In all, 57, 10, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 4 publications
(3 reference statements)
0
21
0
Order By: Relevance
“…22 There are limited data regarding the sonographic appearance of the uterine cavity after a medical abortion; however, more information is available regarding the sonographic appearance of the uterine cavity after a spontaneous abortion or surgical abortion in the first trimester. Bar-Hava et al 23 observed that in 77% of their cases of uterine evacuation in first-trimester TOP, a considerable amount of intrauterine content with various echogenicities was sonographically detected within 1 week of the procedure. Sonographic examinations of these patients following their first menses showed an empty intrauterine cavity.…”
Section: Discussionmentioning
confidence: 99%
“…22 There are limited data regarding the sonographic appearance of the uterine cavity after a medical abortion; however, more information is available regarding the sonographic appearance of the uterine cavity after a spontaneous abortion or surgical abortion in the first trimester. Bar-Hava et al 23 observed that in 77% of their cases of uterine evacuation in first-trimester TOP, a considerable amount of intrauterine content with various echogenicities was sonographically detected within 1 week of the procedure. Sonographic examinations of these patients following their first menses showed an empty intrauterine cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Bar-Hava et al 3 emphasized that on sonography the uterine cavity is seldom empty within 1 week after curettage. They suggested that the presence of varying amounts of irregular intrauterine material should be considered a part of the normal range of the sonographic appearance and does not necessarily indicate the presence of RPOC that require intervention.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Endometrial mass is the most sensitive (79%) and specific (89%) sonographic feature for RPOC. 1,3 Color Doppler flow is more often detected in the endometrium when RPOC are present (75%) than in the absence of RPOC (40%). 1 Complete hydatidiform mole presents as a complex intrauterine mass with multiple anechoic areas of varying sizes (ie, a \snowstorm" appearance).…”
mentioning
confidence: 99%
“…Decisions on patient referral for re-evacuation are based on clinical grounds supported by sonographic findings both of which have high sensitivity but moderate specificity. 2,3,11,18 Dilation and evacuation is a minor surgical procedure; nevertheless, it is associated with complications, which make a strong argument against its possible misuse. 1 We sought to determine the extent of such post factum unnecessary procedures and to delineate factors that might affect the decision to perform re-evacuation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,6 Recently, transvaginal sonohysterography with removal of retained tissue under vision has gained popularity [7][8][9][10] because the ability of a regular sonographic examination to accurately detect retained products of conception has been questioned. [11][12][13] Thus, physicians caring for symptomatic patients who have undergone D&E have to rely on their clinical judgment supplemented by the limited diagnostic capabilities of the sonographic examination to decide between a surgical procedure and continuation of conservative treatment.…”
mentioning
confidence: 99%